2010
DOI: 10.3109/01902148.2010.512972
|View full text |Cite
|
Sign up to set email alerts
|

Safety of sapropterin dihydrochloride (6r–bh4) in patients with pulmonary hypertension

Abstract: The authors investigated the safety of oral tetrahydrobiopterin (BH4), a cofactor for nitric oxide synthesis, as a novel treatment for pulmonary hypertension (PH). Eighteen patients with pulmonary arterial hypertension or inoperable chronic thromboembolic PH received sapropterin dihydrochloride (6R-BH4), the optically active form of BH4, in addition to treatment with sildenafil and/or endothelin receptor antagonists in an open-label, dose-escalation study. 6R-BH4 was administered starting at a dose of 2.5 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
3
25
0
2
Order By: Relevance
“…Redox Signal. 20,[164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182] …”
Section: Introductionunclassified
See 1 more Smart Citation
“…Redox Signal. 20,[164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182] …”
Section: Introductionunclassified
“…Clinical studies examining the effects of xanthine oxidase inhibitors (70,204), tetrahydrobiopterin (sapropterin dihydrochloride [6r-bh4]) (167), and N-acetylcysteine (165) have demonstrated improved vascular function and blood pressure lowering in patients with hypertension, chronic kidney disease, and pulmonary hypertension. However, a recent clinical trial demonstrated that in patients with CAD, oral tetrahydrobiopterin treatment failed to improve endothelial function or cardiovascular outcomes, possibly due to autooxidation of the compound (47).…”
mentioning
confidence: 99%
“…Encouraging results also come from our recent clinical safety study of BH 4 in patients with pulmonary arterial hypertension, where BH 4 treatment at a dosage of 5 mg/kg/day was associated with a positive signal, an increase in 6-minute walk distance, and reduced plasma levels of monocyte chemoattractant protein 1. 42 Collectively, these data suggest that BH 4 supplementation has therapeutic potential for pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 96%
“…The efficacy of the eNOS coupling molecule, the eNOS co-factor sapropterin dihydrochloride, with PH has been assessed in the treatment of patients [60]. The small study of 18 patients monitored markers of NO synthesis, inflammation, exercise capacity and cardiac function [60].…”
Section: Endothelial No Synthase Couplersmentioning
confidence: 99%